Role of statins in primary prevention of cardiovascular disease - Al Ghamdi, Hamed S.; Alkhalaf, Khalaf M.; AlJafen, Ahmad S.; Alotaibi, Mutlaq G.; Algudaihi, Mohammed M.; Alhawiti, Basmah H.; Al Hamad, Fatima F.; Alessa, Abdullah A.; Saif, Ghofran B. Al; Alshammari, Bader T.; Balkhy, Saadiah A. (International Journal Of Community Medicine And Public Health, 2022)
Cardiovascular disease continues to remain a global health challenge due to its increasing trend of prevalence. Almost, 6.2 million deaths were caused by cardiovascular diseases among patients of age range 30-70 years in 2019. The burden of cardiovascular diseases can only be reduced by implementation of effective preventive strategies. Primary prevention is of utmost importance since individuals at risk are treated beforehand thus reducing the chance of development of disease. Statins are lipid lowering agents and are used in primary prevention of cardiovascular disease. The purpose of this research is to review the available information about role of statins in primary prevention of cardiovascular disease. Generally, statins are considered as safe and effective medications to treat and reduce the morbidity of cardiovascular diseases. The relative risk of coronary events, cardiovascular disease mortality, non-fatal strokes, and all-cause mortality is decreased with statin therapy. Elderly population or individuals at risk of development of cardiovascular diseases can be efficiently managed by statin therapy. Some studies associate the occurrence of diabetes with the use of statins but most of the studies recommend the role of statins in prevention as benefits outweigh the risks. Literature also supports the role of statins in primary prevention although more clinical studies in future can yield better evidence-based results to support the use of statins especially in primary prevention.